Mahmoud Hessaby's contribution to the infinitely extended particles theory in quantum physics - Larbani, Sofiane; Othman, Raihan (IIUM Press, 2011)
This chapter aims to highlight quantum physics and its major theories such as the infinitely extended particles. In fact, Classical mechanics functions very well for large objects that are moving much slower than the velocity of light. Nonetheless, once objects start to move very fast, we need to modify Newton's equations by relativistic equations. On the contrary, quantum theory becomes a necessity for objects that are extremely small. In this study, the importance of quantum theory will be investigated and explored. If Newton's laws were to be extended to domains that are far from daily experience, they will start to fail and give incorrect results. Historically, at the tum of the nineteenth century, the failure ofNewtonian physics became very clear in the studies of the Atom (M. Hessaby, 1966).